ENHANCING STUDENTS’ CREATIVE WRITING SKILL THROUGH ENGLISH COMMUNITY - Desi Ratna Sari; Sri Ariani (Ensiklopedia of Journal, 2023)
The objective of this research is to describe the improvement of vocational higher students’ writing skill through creative writing in English Community. The subjects were English Community members who took English for Specific Purposes (ESP) class (AM B) in current academic year. This was a quantitative research in which the data were collected through students’ postings on instagram. There were 28 writings in each cycle scored using Jacob’s scoring writing. The result showed that there was enhancement of students’ writing skill from cycle I, II, and III. Writing through English Community made the students able to improve their English writing skill. However, among 5 writing scoring categories, the writer found that some students have difficulties in language use, vocabulary and mechanics but not for content and organization.